Disruption of normal saline supply chain due to a disaster: an analysis of the impact of normal saline shortage on anesthesia practice in a large hospital system and models toward resiliency - Hussain, Rashid; Pickle, Elizabeth; Lonjin, Taylor; Then, Janine; Rivosecchi, Ryan; Cassavaugh, Jessica; Fichman, Mark; Kaynar, Ata Murat (Frontiers in Medicine, 2026)
ObjectivesIn the wake of the COVID-19 pandemic and upheaval in the global supply chain, the healthcare sector has grappled with acute shortages of essential resources. Such shortages, while intensified recently in scale and frequency, are not new, as disasters have posed recurrent challenges. An illustrative example is the impact of Hurricane Maria, which severely disrupted the production of normal saline (0.9% NaCl fluid bags) from Puerto Rico—the location of about half of the production of saline for the entire United States. Hospitals relying on “just in time” delivery models found themselves in a precarious situation, prompting a need for innovative solutions to sustain care delivery. The occurrence underscores the vulnerability of healthcare infrastructure to external disruptions and emphasizes the need for adaptive strategies to ensure the resilience of individuals and the system in the face of unforeseen challenges.MethodsOur study investigates the impact of Hurricane Maria on saline supplies at the University of Pittsburgh Medical Center (UPMC) and efforts toward building an adaptable model in anesthesia services among providers as well as on a broader, system-wide scale. The study occurred over an 18-month study period, using mixed methods to analyze intravenous (IV) fluid demand and usage patterns before, during, and after the hurricane, integrating qualitative data from 3 months of “participant observation” and survey data.Key findings and conclusionSystem-level adaptation occurred through operating room scheduling, pharmacy-driven standardization, and alternative fluid adoption, while at the individual level, healthcare providers performed drug substitutions, changed mixing practices, and increased reliance on alternative crystalloids. These adaptive measures undertaken at UPMC offer insights for future crises at both the organizational and individual levels within the healthcare system.